Vallásos nevelés és a gyermekkép alakulása a reformáció korában – Feladatok akkor és most - - GORBAI, Gabriella Márta (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2017)
Religious Education and Child Image in the Era of Reformation. Duties Then and Now. The spread of Protestant reformation in Europe brought about a qualitative and quantitative change in schooling. At the same time, the various forms of religious revival changed the parent-child and adult-child relationships as well, which is referable to the fundamental importance attributed to the role of family in religious education. In this study we analyze the view of children in the age of reformation; we try to establish whether the increased attention given to children was indeed prompted by religion; we look for the explanation of the fact that protestant communities have shown a form of care that was different from what was customary before that time. As a conclusion we can draw comparison between then and now, since our problems, aims and tasks regarding the realization of religious education are in many ways similar to the challenges faced by our great ancestors in the age of reformation.